2015
DOI: 10.5194/aab-58-387-2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary soybean and sunflower oils with and without L-carnitine supplementation on growth performance and blood biochemical parameters of broiler chicks

Abstract: Abstract. An experiment was designed to investigate the effects of soybean, sunflower oil and dietary Lcarnitine supplementation on growth performance, some blood biochemical parameters and antibody titer against Newcastle disease of broiler chicks. A 5-week feeding trial, 240 1-day old male broiler chicks (Ross 308) were randomly allocated to six dietary treatments as a 3 × 2 factorial experimental design where three sources of dietary oil contained soybean, sunflower and soybean plus sunflower oil with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
4
21
0
Order By: Relevance
“…Bodyyyyyy weight gain of broiler chickens were significantly reduced by dietary conjugated linoleic acid (Szymczyk et al, 2001, Zduńczyk et al, 2001Shahriar et al, 2007). Sunflower oil has the higher percentage of linoleic acid (C18 : 2, ω-6), as omega 6 fatty acids and therefore this plant oil has the lower ω-3 to ω-6 fatty acid ratio in comparison to soybean oils (Jalali et al, 2015). Also, Fernandez-Carmona et al (1998) reported that increasing the level of dietary fat did not increase average daily gain.…”
Section: Growth Performance and Feed Efficiencymentioning
confidence: 99%
“…Bodyyyyyy weight gain of broiler chickens were significantly reduced by dietary conjugated linoleic acid (Szymczyk et al, 2001, Zduńczyk et al, 2001Shahriar et al, 2007). Sunflower oil has the higher percentage of linoleic acid (C18 : 2, ω-6), as omega 6 fatty acids and therefore this plant oil has the lower ω-3 to ω-6 fatty acid ratio in comparison to soybean oils (Jalali et al, 2015). Also, Fernandez-Carmona et al (1998) reported that increasing the level of dietary fat did not increase average daily gain.…”
Section: Growth Performance and Feed Efficiencymentioning
confidence: 99%
“…Sunflower oil has the higher percentage of linoleic acid (C18: 2, n-6), as n-6 fatty acids. This plant oil has the lower n-3 to n-6 fatty acid ratio in comparison to soybean oils (Jalali et al, 2015). The recorded improved ADG might be due to the presence of poly-unsaturated fatty acids (PUFA) in vegetable oils (El-Sayed et al, 2013).…”
Section: Total Weight Gainmentioning
confidence: 99%
“…This effect is highly associated with down-regulation or up-regulation of different cytokines that are believed to affect the avian immune function such as IL-1β, IFN-γ, MGF, IL-1, IL-4, IL-2 [13,14].…”
Section: Involvement In Avian Immune Functionmentioning
confidence: 99%